Bibliometric analysis of foreign direct investment and economic growth relationship. A research agenda - Cicea, Claudiu; Marinescu, Corina (Journal of Business Economics and Management, 2021)
The relationship between foreign direct investment and economic growth is a relationship that has long been studied in the economic literature, of particular importance for the economic and social development of any nation. The main objective of this paper is to analyze the scientific output in this scientific area, based on a bibliometric analysis, in order to identify some trends and to explain some phenomena within the economic reality.The paper analyzed 2281 documents from the Scopus database, using tools provided by the aforementioned database, VOSViewer and Citespace software. The analysis was carried out on several levels: typology of information dissemination, thematic area of publications, temporal/geographical distribution of documents and their scientific content.Among the findings authors can mention that the connection between foreign direct investment and economic growth is very strong (according to the cluster analysis in VOSViewer); consequently, the focus of the authors migrated from general economic aspects of the relationship to the elements of ecology and environmental protection. Going deeper with the analysis, conducting two parallel analysis of the papers with highest citation burst and keywords with highest citation strength values, some interesting trends were found in the relationship between foreign direct investment and economic growth.First published online 29 December 2020